Phase II randomized sham-controlled study of renal denervation for individuals with uncontrolled hypertension – WAVE IV. Issue 3 (March 2018) - Schmieder, Roland E.; Ott, Christian; Toennes, Stefan W.; Bramlage, Peter; Gertner, Michael; Dawood, Omar; Baumgart, Peter; O'Brien, Benjamin; Dasgupta, Indranil; Nickenig, Georg; Ormiston, John; Saxena, Manish; et al.
Abstract : Objectives: The aim of this double-blind, randomized, sham-controlled study was to verify the blood pressure (BP)-lowering efficacy of externally delivered focused ultrasound for renal denervation (RDN). Background: Nonrandomized, first proof-of-concept study and experimental evidence suggested that noninvasive techniques of RDN emerged as an alternative approach of RDN to invasive technologies. Methods: WAVE IV, an international, randomized (1 : 1) sham-controlled, double-blind prospective clinical study, was prematurely stopped. Patients were enrolled if office BP was at least 160 mmHg and 24-h ambulatory BP was at least 135 mmHg, while taking three or more antihypertensive medications. The treatment consisted of bilateral RDN using therapeutic levels of ultrasound energy and the sham consisted of bilateral application of diagnostic levels of ultrasound energy. Results: In the 81 treated patients neither changes in office BP at 12 and 24 weeks, nor changes in 24-h ambulatory BP at 24-week follow-up visit differed between the two groups significantly. Of note, no safety signal was observed. Adherence analysis disclosed full adherence in 77% at baseline and 82% at 6 months' follow-up visit. Post hoc analysis revealed that stricter criteria for stabilization of BP at baseline were associated with a numerically greater change in 24-h ambulatory BP in the RDN group than in the sham group. Conclusion: Our data did not prove that antihypertensive efficacy of the externally delivered focused ultrasound for RDN was greater than the sham effect. Stabilization of BP at baseline was identified as an important determinant of BP changes. Abstract : Supplemental Digital Content is available in the text